An integrated RNA‐Seq and network study reveals the effect of nicotinamide on adrenal androgen synthesis. (9th February 2020) - Gao, Xueying; Yu, Zhiheng; Yang, Jie; Gao, Yutong; Li, Shumin; Zhang, Wei
Abstract: Acne vulgaris is a chronic inflammatory disease of the skin resulting from androgen‐induced increased sebum production and altered keratinization. Nicotinamide (NAM), an amide form of vitamin B3 with a well‐established safety profile, has shown good therapeutic potential in treating acne and its complications. NAM has anti‐inflammatory effects and reduces sebum but its function in androgen biosynthesis remains unknown. In this study, we used a widely used cell model, starved human adrenal NCI‐H295R cells, to examine the effects of NAM in androgen production and its mediated network changes. By treating NCI‐H295R cells with 1‐25 mmol/L of NAM, we found that cell viability was only slightly inhibited at the highest dose (25 mmol/L). NAM reduced testosterone production in a dose‐dependent manner. Transcriptomic analysis demonstrated that key enzymes of androgen biosynthesis were significantly decreased under NAM treatment. In addition, gene set enrichment analysis (GSEA) showed that gene sets of cell cycle, steroid biosynthesis, TGFβ signalling, and targets of IGF1 or IGF2 were enriched in NAM‐treated cells. Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway and Gene ontology (GO) analysis of the differentially expressed genes also suggested that steroidogenesis and SMAD signalling were affected by NAM. Overall, these crucial genes and pathways might form a complex network in NAM‐treated NCI‐H295R cells and result in androgen reduction. These findings help explain the potential molecular actions of NAM in acne vulgaris, and position NAM as a candidate for the treatment of other hyperandrogenic disorders.